Accessible Phreatic Groundwater Resources in the Central Shijiazhuang of North China Plain: Perspective From the Hydrogeochemical Constraints - Yong Xiao; Dian Xiao; Qichen Hao; Kui Liu; Kui Liu; Rui Wang; Xun Huang; Xin Liao; Yunhui Zhang; Yunhui Zhang (Frontiers in Environmental Science, 2021)
Phreatic groundwater plays a significant role in the water supply for human communities, especially in water scarce regions. This research was conducted to investigate the hydrochemistry and contamination of phreatic groundwater and their constraints on drinking water supply in a semiarid region of the North China Plain. A total of 49 phreatic groundwaters were collected for the hydrochemical analysis. The results suggested the phreatic groundwater had a slightly alkaline nature. Although the groundwater had a large variation of salinity with the TDS of 172–1,875 mg/l, most groundwater was moderately-hard fresh and of HCO3-Ca type. Contaminants of NO3−, NO2−, NH4+, Fe, F−, Zn, Mn were detected, but only NO3−, NO2−, NH4+, and Fe were found exceeding the drinking water desirable limits at some sites. The nitrogen contaminants were from anthropogenic inputs (urban sewage effluents and agricultural fertilizers) and mainly distributed in the central study area. The anthropogenic inputs of nitrogen contaminants also elevated groundwater salinity. Among the exceeding contaminants, only NO3− would pose a potential health risk to water consumers. The existing health risks by NO3− ranged from medium risk (HQ of 1–4) to high risk (hazard quotient > 4) for all populations, and most risks were categorized into the medium risk rank. Groundwater F− was also found with health risk at some sporadic sites although it did not exceed, only approached, the desirable limit. Its health risk was only to infants and categorized into the medium risk with the maximum HQ of 1.55. Most phreatic groundwater (83.67%) in the study area had relatively good quality and was suitable for domestic usage with the EWQI value below 150. Others belonged to the poor (EWQI of 150–200) and extremely poor (EWQI > 200) quality categories, and mainly distributed in the urban Gaocheng. Thus, it is recommended to pay attentions to the anthropogenic contaminants inputs into phreatic aquifers in human activities areas.